The AP-1 site is required for basal expression but is not necessary for TPA-response of the human stromelysin gene. - Buttice, G (1991)
We have studied the activity of the AP-1 site, a target for the Fos and Jun family of transcription factors, in the context of the human stromelysin promoter (-1303 to +4). In transiently transfected human HepG2, HeLa and fibroblast cell cultures, point-mutations in any position of the stromelysin AP-1 sequence TGAGTCA (-70 to -64) reduced both the basal level and TPA-induced expression from the stromelysin promoter. TPA-induction fold of the mutant promoters, however, was comparable to that of the wild-type promoter. Similarly, antisense c-Fos mRNA expression reduced basal activity but had no significant effect on the relative TPA-response of the stromelysin promoter. Further, in mouse F9 cells cotransfected with c-Fos and c-Jun expression plasmids, the transfected wild-type stromelysin promoter activity was increased 57-fold whereas no transactivation was detected for an AP-1 mutant stromelysin promoter. In gelshift assays, stromelysin promoter fragments (-101 to -11), containing the mutated AP-1 site, all failed to bind or compete for the in vitro synthesized Fos and Jun proteins. We interpret these data to suggest that the Fos and Jun proteins, or similar activity, and the AP-1 site are required for the basal level expression of the human stromelysin gene. Strikingly, these data also suggest that the stromelysin AP-1 site is not necessary for the TPA-response.